Measurement invariance of the Center for Epidemiological Studies-Depression scale and associations with genetic risk in older adults - Saari, Toni T.; Piirtola, Maarit; Aaltonen, Aino; Palviainen, Teemu; Varjonen, Anni; Julkunen, Valtteri; Rinne, Juha O.; Kaprio, Jaakko; Vuoksimaa, Eero (Public Library of Science (PLoS), 2026)
Background
As populations are aging, it needs to be ensured that valid depression rating scales are available across old adulthood. Center for Epidemiological Studies-Depression scale (CES-D) is a common depression rating scale, however, few studies have assessed its validity in individuals with age over 90 and/or cognitive impairment. We examined the factor structures of 20-, 15-, and 8-item CES-D scales, their measurement invariance for age and cognition, and associations with genetic risk of depression.
Methods
Participants were from a population-based older Finnish Twin Cohort study including 71–79-year-olds from the MEMTWIN II (n = 1034 for exploratory and n = 664 for confirmatory factor analyses) and 90+ year-olds from the NONAGINTA (n = 134, confirmatory factor analyses) sub-studies. Associations of polygenic risk score of major depressive disorder (MDD-PRS) with CES-D scales were examined in MEMTWIN II.
Results
Exploratory factor analyses (n = 1034) suggested four- (CES-D 20) and three-factor (CES-D 8) structures and these models fit well in confirmatory analyses (n = 664). Unidimensional models had good (CES-D 15 & 20) or fair fit (CES-D 8). Results supported scalar invariance of all CES-D versions for age and cognitive status. Higher MDD-PRS was associated with more depressive symptoms in different CES-D versions.
Conclusions
Different CES-D versions are adequate for measuring depressive symptoms across age groups and cognitive spectrum in old age. Genetic risk of depression predicts depressive symptoms even in old age.